Hits and Misses: Leveraging tDCS to Advance Cognitive Research - Berryhill, Marian E.; Peterson, Dwight J.; Jones, Kevin T.; Stephens, Jaclyn A. (Frontiers in Psychology, 2014)
The popularity of non-invasive brain stimulation techniques in basic, commercial, and applied settings grew tremendously over the last decade. Here, we focus on one popular neurostimulation method: transcranial direct current stimulation (tDCS). Many assumptions regarding the outcomes of tDCS are based on the results of stimulating motor cortex. For instance, the primary motor cortex is predictably suppressed by cathodal tDCS or made more excitable by anodal tDCS. However, wide-ranging studies testing cognition provide more complex and sometimes paradoxical results that challenge this heuristic. Here, we first summarize successful efforts in applying tDCS to cognitive questions, with a focus on working memory (WM). These recent findings indicate that tDCS can result in cognitive task improvement or impairment regardless of stimulation site or direction of current flow. We then report WM and response inhibition studies that failed to replicate and/or extend previously reported effects. From these opposing outcomes, we present a series of factors to consider that are intended to facilitate future use of tDCS when applied to cognitive questions. In short, common pitfalls include testing too few participants, using insufficiently challenging tasks, using heterogeneous participant populations, and including poorly motivated participants. Furthermore, the poorly understood underlying mechanism for long-lasting tDCS effects make it likely that other important factors predict responses. In conclusion, we argue that although tDCS can be used experimentally to understand brain function its greatest potential may be in applied or translational research.